Phytochemical Characterization of Persicaria longiseta Inflorescence Biomass and Its Biological Activities - Abeer S. Meganid; Mohamed Abdel-Aal Amin (BioResources)
Nutritional values and biological activity of Persicaria longiseta inflorescence extract (PLE) were assessed relative to the antioxidant, anticancer, and antibacterial impact of ethanolic extracts from the plant’s inflorescence. Using high-performance liquid chromatography (HPLC), the PLE ethanolic extract revealed that naringenin, chlorogenic acid, quercetin, rosmarinic acid, rutin, and gallic acid were all present in high concentrations (9780, 8250, 5190, 4320, 2520, and 2430 µg/g, respectively). Nutritional values assessment showed carbohydrates (166 mg/g), protein (53.2 mg/g), phenols (36.2 mg/g), and flavonoids (13.2 mg/g). When applied to pathogen species and cancer cells, the ethanolic extract of PLE showed inhibitory effects. Additionally, the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were evaluated for the tested microorganisms. The P. longiseta extract exhibited significant inhibition of hemolysis, particularly in the presence of B. subtilis (77.7, 90.8, and 95.9%) compared to K. pneumonia (54.1 ± 1.16, 75.8, and 85.3%) at varying doses (25, 50, 75% MIC, respectively). These results represent the beginning of the use of this extract in advanced medical aspects as an antimicrobial, antioxidant, antihemolytic, and antitumor agent, with some confirmatory and accurate experiments in vivo.